The Influence of Investment and Company Growth on Increasing Firm Value Through Profitability - Imelda Fadilah; Muhadjir Anwar (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The purpose of this research is to analyze the effect of investment and firm growth on the improvement of firm value, with profitability serving as a mediating factor. This study employs a quantitative research design using secondary data obtained from the Indonesia Stock Exchange (IDX). The population includes infrastructure sector companies listed on the IDX from 2021 to 2023, and purposive sampling was applied to select 29 companies, yielding a total of 87 firm-year observations. Path analysis with SPSS software was used to test the hypotheses and examine both direct and indirect relationships among the variables. The findings reveal that investment has a significant positive impact on firm value, indicating that firms with higher levels of investment tend to enhance their market valuation. Similarly, firm growth contributes positively to firm value, suggesting that sustainable expansion fosters greater investor confidence. Moreover, profitability is proven to mediate the relationship between investment and firm value, showing that the benefits of investment are maximized when they lead to improved profitability. Profitability also significantly mediates the relationship between firm growth and firm value, underscoring its role as a key driver in translating growth strategies into shareholder value. These results highlight the importance of profitability as a strategic element in strengthening firm value. Practically, the study suggests that managers should prioritize profitable investments and sustainable growth strategies to maximize firm value, while investors may consider profitability as a central indicator when evaluating firm performance.